2005
DOI: 10.4102/ojvr.v72i4.183
|View full text |Cite
|
Sign up to set email alerts
|

Association of trypanosomosis risk with dairy cattle production in western Kenya

Abstract: <span style="font-family: arial,helvetica;">Dairy cattle reared in western Kenya are exposed to medium to high levels of trypanosomosis risk. The social background, farm characteristics and dairy cattle productivity of 90 and 30 randomly selected farmers from medium- and high-risk trypanosomosis areas, respectively, were compared. All the 120 farmers were visited between July and August 2002. Data analysis was performed using descriptive statistics and analysis of variance. The results showed that increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…These were identified as being responsible for the high DA and ISM resistance in the community [10]. Similar reports have been reported in Kenya, where 73% (475/650) of treatments were done by untrained personnel [12]. A high degree of variation in trypanocide usage and the intervals of their application (i.e., 20% of respondents rely on trypanocide for trypanosomiasis control [5] in Tanzania) have been reported, demonstrating an absence of standard treatment regiments.…”
Section: Meta-analysis On Community Practices and Control Measures Ag...supporting
confidence: 60%
See 2 more Smart Citations
“…These were identified as being responsible for the high DA and ISM resistance in the community [10]. Similar reports have been reported in Kenya, where 73% (475/650) of treatments were done by untrained personnel [12]. A high degree of variation in trypanocide usage and the intervals of their application (i.e., 20% of respondents rely on trypanocide for trypanosomiasis control [5] in Tanzania) have been reported, demonstrating an absence of standard treatment regiments.…”
Section: Meta-analysis On Community Practices and Control Measures Ag...supporting
confidence: 60%
“…In Tanzania, farmers reported unavailability of drugs, lack of initiative to control the disease in the community, poor knowledge, and lack of veterinary services as well as financial constraints as major drivers for the abuse of trypanocides [5] while in Ethiopia, DA was preferred over ISM since it was cheaper, easy to use and access [15]. In western Kenya, improved farmers' knowledge (see [17] following over 40 years of interactions with the same compounds) on trypanocides was associated with a poor prognosis in farmer-led-animal treatments, leading to the development of trypanocide resistance in the herds [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypanosomiasis costs Africa about US$4.5 billion a year compared to East Coast fever (ECF) losses of about US$168, million (Budd, 1999;Kristjanson et al, 1999). In Kenya, increased trypanosomiasis risk represented by an increased disease prevalence from 1 % to 20 % has been shown to decrease the density of cattle by about 53 %, and is associated with an increase of calving interval from about 14 to 25 months among the dairy farmers (Mugunieri and Matete, 2005).…”
Section: Relative Importance and Preference For Trypanotolerance Cattle Traitmentioning
confidence: 99%
“…The values were estimated based on a review of longitudinal and cross-sectional studies comparing the productivity observed in infected and uninfected individual cattle or whole herds, under conditions of both high and low trypanosomiasis challenge (see Section 2.3.3). The effects of trypanosomiasis treatment on performance were estimated based on a review of longitudinal and cross-sectional studies comparing the productivity observed in infected and uninfected individual cattle or whole herds, under conditions of both high and low trypanosomiasis challenge [33,45,[54][55][56][57][58][59][60][61]. The review gave a range of values for the effect of the disease.…”
Section: Parameterising the Cattle Production Systemsmentioning
confidence: 99%